RLSA UNTUK SEGMENTASI PLAT MOBIL DAN PROSES PENGENALAN DENGAN BACKPROPAGATION - Kristina Erlinda; Agus Budi (Jurnal Ilmu Komputer dan Sistem Informasi, 2015)
The development of knowledge in the field of artificial intelligence so advanced, such as research on licenze plate recognition. The design of this application has the purpose to recognize the license plate number of the car. Number plate segmentation using Run Length Smearing Algorithm and introduction of each character on a plate by using Backpropagation. Input as the image of the front or rear of the car were taken with a digital camera. With 50 test images, which successfully identified the perfect amount to ten plates (28%  success rate). Key wordsRun Length Smearing Algorithm, Backpropagation